Risk Factors Associated with Early Onset of Sepsis - Nadeem Shahzad, Sohail Shahzad, Wahab Qadir, Anjum Ali, Safia Khan, Arshad Rafique, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Neonatal sepsis (EOS) is among one of the leading cause of death that usually occurs due to infection in the first month of life and can be the result of various maternal and neonatal contributing factors. Objectives: To determine maternal and neonatal contributing factors for early onset of sepsis in neonates. Study design: cross sectional study Period: From 13th April 2019 to 12th Oct 2019. Settings: Neonatal units of pediatric medicine of central park teaching hospital Lahore and Bhatti international hospital Kasur. Material and methods: After approval from hospital ethical committee total 151 neonates were selected using non-probable consecutive sampling. Neonates of both gender who were having gestational age >30 weeks with early onset sepsis were enrolled. Patients who had received antibiotics before presentation were excluded. 5ml of venous blood after proper sterilization was taken from all patients and sent to hospital laboratory for WBC count, CRP and blood culture. Data was entered in pre-designed Performa and analyzed using SPSS 20. Results: There were total 151 patients in study, minimum and maximum age was 1 day and 7 days respectively with mean age of 3.66±1.88 days. Mean gestational age was 35.5±2.6 weeks and mean birth weight was 2.2±1.4 kg. There was slight increase in female patients 51% and 49% males. Among maternal contributing factors maternal fever was found in 64.9%, premature rupture of membrane was found in 43%, foul smelling liquor in 37.1% and meconium-stained amniotic fluid was found in 33.1% neonates. Among neonatal contributing factors prematurity was found in 66.2% low birth weight was present in 64.2%, and low APGAR score was present in 56.6 % neonates. Data was stratified for gender and contributing risk factors but p value was not statistically significant. Data was stratified for gestational age and p value was significant for prematurity, low birth weight and offensive smelling liquor. Conclusion: Prematurity, low birth weight, low APGAR score and maternal fever were significant contributing factors in EOS. Keywords: EOS, Neonatal contributing factors, Maternal contributing factors